Research on a Four-Quadrant Converter Control Strategy of Locomotive Based on Synchronous Sampling - Zhibo CHEN; Jing SHANG; Zhixue ZHANG; Wenqing MEI; Jian GAO (机车电传动)
A four-quadrant converter control strategy of locomotive based on synchronous sampling was studied, and the adopted carrier generation scheme and synchronous modulation strategy were introduced. The MATLAB simulation and grid measurement results showed that this method could effectively reduce the harmonic content of AC input current of the locomotive to improve the current quality.